Influence of rubber content of concrete on local impact damage - Lim, Natalie Sze (2018)
The disposal and management of waster has been a pertinent issue in numerous countries and one of the main challenges is the disposal of unused vehicles tyres. To ease the course of waste management, many studies have been directed to look at the diverse potentials of disposing the tyre wastes. One of the most hopeful answers is to reutilize the tyre rubber in cement concrete. The objectives of this project are to assess the engineering properties of plain concrete and rubberized concrete and examined their possible engineering applications. Replacing 20% of course aggregate by volume with rubber crumbs (from rubber track and rubber tyres) was found to be the optimum rubberized concrete mix to achieve a compressive strength of 35 MPa which is required for most structural applications. Two different sizing of cylindrical specimens were casted to in order to conduct static compressive strength test using a universal compressive test machine and dynamic impact test using the Split Hopkinson Bar Test. Results from the static test indicate that the mechanical properties such as the compressive strength of the rubberized concrete was significantly reduced as compared to the plain concrete. As for the impact loadings on the cylinder specimens were studied to better understand the collision behaviour of rubberized concrete when exposed to dynamic impact.